Improving Energy Efficiency in Flavor Enhancer Production Using an Integrated Lean Manufacturing and Energy Value Stream Mapping Approach - Ahmad Habib Ramadhana; Putu Dana Karningsih (Universitas Panca Marga, 2026)
The flavor enhancer industry faces significant challenges in improving energy efficiency because steam, electricity, and cooling utilities contribute approximately 16% of the Cost of Goods Manufactured (COGM). Although Lean Manufacturing has been implemented, most improvement initiatives have focused on production output and defect reduction rather than energy efficiency. This study aims to identify and reduce operational and energy waste in the Refinery unit using the Energy Value Stream Mapping (EVSM) approach. The proposed framework integrates EVSM for process and energy flow mapping, the Dotoli Matrix for critical waste prioritization, Root Cause Analysis using the 5 Whys method for identifying the underlying causes of waste, and Heat Exchanger Network (HEN) analysis for evaluating energy recovery opportunities, thereby providing a comprehensive approach to energy mapping, waste prioritization, root cause identification, and energy recovery evaluation. The results indicate that the dominant wastes are excessive cooling energy consumption and defect waste caused by delayed thin broth handling. Improvement proposals were developed through Heat Exchanger Network integration by utilizing glutamic mother liquor-1 as an internal cooling medium, generating potential savings of IDR 1,229,384,800 per year with a payback period of 2.4 years. In addition, the implementation of an automatic spray ball system reduced tank cleaning time from 49 minutes to 19 minutes and generated potential savings of IDR 274,007,580.52 per year. The study demonstrates that integrating Lean Manufacturing and EVSM effectively reduces energy consumption and operational waste in the Refinery unit.